Neurotoxic potential of trichlorfon to multiple sublethal doses in wistar rats (2013)
The organophosphates used for pest control induce sensory, motor and psychiatric disturbances after chronic exposure. The ester type is the cause of the intermediate syndrome and delayed neuropathy, in which the white and gray matter in the brain are severely affected.The aim of this study was to evaluate the effect of multiple sublethal doses of Trichlorfon on neurons, astrocytes and myelinated tissue in a rat model of brain neurotoxicity. Trichlorfon (metrifonate) was administered to adult Wistar rats at doses of 11 or 22 μg/kg by oral gavage every seven days for four or eight weeks (four experimental groups) and a control group (placebo). One week after the last dose, animals were euthanized and the brains perfused, removed and cut into coronal segments of 50 μm of thickness by using a vibratome. The sections were analyzed by immunohistochemistry, using markers of neuronal survival, astrocytic reactivity and the myelin basic protein. Neuronal and astrocytic reactivity were significantly reduced in Trichlorfon-treated animals relative to controls, whereas myelin reactivity was significantly increased, with abnormal distribution of myelin in white matter. The results suggest a neurotoxic damage of Trichlorfon on neuronal and astrocyte functional balance and abnormal myelin formation consequent to the cell damage.